Analisis Pendekatan Plan-Do-Check-Act (PDCA) Pada Program Tahsin Quran di Perguruan Tinggi - Ma`sum, Ali; Sa`diyah, Maemunah (Universitas Muhammadiyah Makassar, 2025)
The aim of this research is to analyze the implementation of the Tahsin Quran program at YARSI University using the plan-do-check-act (PDCA) approach. This research is qualitative research. Research data was collected using interview and documentation techniques and then analyzed using descriptive analysis. From the results of this research, it was found that the implementation of the Tahsin Quran program as part of continuous improvement has followed the PDCA cycle. In planning (plan), Ruhul Islam division identifies problems, sets goals and determines the resources involved. In implementation (do), the Ruhul Islam division collaborates with the Tahsin Quran institution and supervises their activities in accordance with the plans that have been made. In checking (check), the Ruhul Islam division supervises the learning of the Quran in the zoom room and during the final exam (post-test). At the action stage (Act), the Ruhul Islam division will carry out a follow-up to the Tahsin Quran program which includes time, systems, supporting activities, and optimizing the involvement of PAI lecturers